1999
DOI: 10.1159/000025680
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependence of Functional Alterations in Mesenteric Arteries from the Aldosterone-Salt Hypertensive Rat

Abstract: We tested the hypothesis that an elevated potassium-42 (42K+) efflux (highly dependent on Ca2+) and an increase in the sensitivity of contraction and 42K+ efflux to norepinephrine (NE) in conduit arteries of aldosterone-salt hypertensive rats (AHR) exended to smaller, distributing arteries. Functional endpoints were compared in two sizes of arteries from the mesenteric bed: second-order branches of the superior mesenteric artery (SMA branches) and the SMA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…(1996) suggested that the resistance vasculature, which is critical to the control of peripheral resistance, might not show the same functional alterations as those expressed in large conductance arteries. Thus, considering that in our previous study ( Lemos et al ., 1999 ) we employed aortic preparations which are conductance arteries ( Magliola & Jones, 1999 ) and likely would contribute little to the decrease in peripheral resistance seen after dioclein, it is plausible to propose that the hypotensive effect produced by the flavonoid in conscious normotensive rats is, at least, secondary to a vasorelaxant effect on resistance vessels.…”
Section: Discussionmentioning
confidence: 99%
“…(1996) suggested that the resistance vasculature, which is critical to the control of peripheral resistance, might not show the same functional alterations as those expressed in large conductance arteries. Thus, considering that in our previous study ( Lemos et al ., 1999 ) we employed aortic preparations which are conductance arteries ( Magliola & Jones, 1999 ) and likely would contribute little to the decrease in peripheral resistance seen after dioclein, it is plausible to propose that the hypotensive effect produced by the flavonoid in conscious normotensive rats is, at least, secondary to a vasorelaxant effect on resistance vessels.…”
Section: Discussionmentioning
confidence: 99%